Nursing Now campaign and its impact on nursing education in a federal university - Rúbia Knobeloch dos Santos; Eluiza Macedo; Bárbara Rodrigues Araujo; Ana Amélia Antunes Lima; Graciele Fernanda da Costa Linch; Rita Catalina Aquino Caregnato (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To report the actions developed by a group in the Nursing Now campaign and its impact on nursing education. Method: It is an experience report about the execution of the work group formed by nurse professors, nursing academics and master's students at a federal university in Brazil focusing on the Nursing Now campaign, developing actions in the second half of 2019. Results: The actions developed involve the creation of a work group and the active participation of the group in four major events resulted in the visibility and appreciation of the work developed by the profession. Conclusion: The organized group promoted actions that had a positive impact inside and outside the University, expanding visibility to the profession and the actions developed. The academic environment, associated to the worldwide mobilization of the campaign, promoted a favorable context for the debate about the valorization of the category and leadership in nursing.